Modeling the Leaching of Cobalt and Manganese from Submarine Ferromanganese Crusts by Adding Steel Scrap Using Design of Experiments and Response Surface Methodology - Kevin Pérez; Norman Toro; Mauricio Mura; Manuel Saldana; Felipe M. Galleguillos Madrid; Iván Salazar; Francisco Javier González; Egidio Marino; Jonathan Castillo; Ignacio Castillo; Pía C. Hernández (Applied Sciences)
Due to the scarcity of high-grade minerals on the Earth’s surface and the ever-increasing demand for critical metals required in the production of clean energy, the search for alternative sources has become essential. Ferromanganese crusts, a mineral resource located in the depths of the ocean, contain high concentrations of valuable metals, particularly cobalt (Co) and manganese (Mn). A leaching process using sulfuric acid, with the addition of steel scrap, has been proposed for processing this resource. The study investigated the extraction of manganese (Mn) and cobalt (Co) under acidic conditions at 25 °C, employing a factorial experimental analysis. Statistical models were adjusted using response surface methodology to evaluate the effects of time and the ferromanganese crust/Fe(res) (iron residue) ratio as predictive variables. The results demonstrated that the extraction of Mn and Co could be effectively modeled through multiple regression, with strong goodness-of-fit indicators. Optimal extraction was achieved at extended durations (30 min) and lower ferromanganese crust/Fe(res) ratios (1/3) for the sampled values. Gradient analysis revealed that extraction efficiency was directly proportional to time and inversely proportional to the ferromanganese crust/Fe(res) ratio, except in the case of Co extraction at higher durations and lower ratio levels. Additionally, no precipitation of Mn or Co species was observed in the analyzed residues.